Beyond Freeports: Revitalising Britain with self-governing cities - Vera Kichanova (Institute of Economic Affairs (IEA), 2025)
The Freeports strategy announced by the previous government attempted to address today's challenges with yesterday's recipes, lacked the necessary deregulatory framework and failed to address key issues such as the housing crisis. This paper proposes an alternative: a new generation of 'Hong Kong-style' self-governing cities with broad autonomy to experiment with diverse planning regimes, governance models and investment strategies. From the City of London to Canary Wharf, Britain is the cradle of urban self-governance. Across the globe, British institutions continue to create urban miracles - consider Hong Kong or the financial hubs in Dubai and Qatar, which adopted English common law and became magnets for investment. The paper explores historical and contemporary examples of such regions, from the Hanseatic League to emerging charter cities, demonstrating how these models contribute to prosperity and economic revitalisation. Self-governing regions are on the rise in emerging economies, where they often struggle with the very institutional instability they seek to overcome. The UK, with its strong institutions of democracy, property rights and rule of law, is well-positioned to lead a new era of self-governing urban development, potentially creating multiple new 'Hong Kongs' within its borders. Healthy competition between such cities would help identify the most effective solutions, which could then be scaled and replicated nationwide.
Keywords: 330